A história do currículo de zoologia no curso de formação de professores de ciências biológicas da UFMS – Campus Campo Grande - Lopes, Zielma de Andrade (2022)
This thesis is part of the field of curriculum research, with a qualitative approach and has as a goal investigating the Zoology curriculum for the preparing of Science and Biology teachers, at Campo Grande's UFMS from 1981 to the current day, through a historical-social perspective. To do so, we analyzed official historical documents and texts about the Zoology curriculum (vertebrates and invertebrates) during the aforementioned period, in the Biological Sciences teaching major at UFMS, creating a parallel with the historical-social context of Brazil. We referenced the work of scholars in the areas of Curriculum and History of School Subjects, which are founded on the theories of social-historical construction of classes, in particular authors such as Ivor Goodson, Márcia Ferreira and Andrè Chervel. Due to the period chosen for research, the focus of the analysis was on reading about the prescriptive dimensions of the curriculum and its organization, paying attention to norms and breaks, and the historical context on which they occurred, according to the methodology proposed by analysis of Orlandi's Discourse (2015). Despite Zoology's importance, not only due to knowledge about biodiversity and environmental affairs that involve all living organisms, but also by matters of applicability in development and research of new technologies, we noticed the tiny amount of works that propose to discourse about its history and changes that took place in its curriculum. On the works that mentioned it, they limited themselves to speaking about the changes that took place from the 20th century during the unification of the school subject of Biological Sciences in the curriculum of primary and secondary schools at the time. It becomes even more worrying when these discussions are not present in curriculum research about preparing teachers. Regarding the subject in UFMS's Campo Grande campus's Biological Sciences, we found that a lot of its workings were strongly tied to Naturalist traditions and lately finds itself in a movement of change and reestructuring.